The Effect of Gender Differences on Psychological Well-being of Lecturers - Yudiani, Ema; Meyrinda, Jesyia; Khosiyah, Siti; Dendara, Husna (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2024)
Previous studies on gender differences in mental health has reported significantly different results. Inconclusive results have also been obtained from existing literature focused on differences in psychological well-being in organizations and industries between women and men. Therefore, this study aims to determine the effect of gender differences on psychological well-being of state Islamic religious universities lecturers. The study procedures were carried out with a quantitative method, focusing on 652 lecturers from Indonesian state Islamic universities. The selected respondents were assessed with the Ryff Psychological Well-Being Scale and the Bem Sex Role Inventory. The data obtained were then analyzed using MANOVA to determine differences between 2 gender groups, namely male and female. The results showed that there were significant gender differences in psychological well-being between male and female lecturers at state Islamic religious universities. In terms of autonomy and self-acceptance, men outscored women, while in terms of personal growth and positive relationships with others, women had higher scores. In addition, high masculinity was the most significant factor in both men's and women's psychological well-being.